Translating research on quality improvement in five European countries into a reflective guide for hospital leaders: the 'QUASER Hospital Guide'. (12th June 2019) - Anderson, Janet E; Robert, Glenn; Nunes, Francisco; Bal, Roland; Burnett, Susan; Karltun, Anette; Sanne, Johan; Aase, Karina; Wiig, Siri; Fulop, Naomi J; ,
Abstract: Objective: The aim was to translate the findings of the QUASER study into a reflective, dialogic guide to help senior hospital leaders develop an organization wide QI strategy. Design: The QUASER study involved in depth ethnographic research into QI work and practices in two hospitals in each of five European countries. Three translational stakeholder workshops were held to review research findings and advise on the design of the Guide. An extended iterative process involving researchers from each participant country was then used to populate the Guide. Setting: The research was carried out in two hospitals in each of five European countries. Participants: In total, 389 interviews with healthcare practitioners and 803 hours of observations. Intervention: None. Main outcome measure: None. Results: The QUASER Hospital Guide was designed for leadership teams to diagnose their organization's strengths and weaknesses in the eight QI challenges. The Guide supports organizational dialogue about QI challenges, enables leaders to share perspectives, and helps teams to develop solutions to their situated problems. The Guide includes extensive examples of QI strategies drawn from the data and is published online and on paper. Conclusions: The QUASER Hospital Guide is empirically based, draws on a dialogical approach to Organizational Development and complexity science and can facilitate hospital leadership teams to identify the best solutions for their organization.